The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2004
DOI: 10.1109/jlt.2004.825237
|View full text |Cite
|
Sign up to set email alerts
|

PMD-Induced Fluctuations of Bit-Error Rate in Optical Fiber Systems

Abstract: Abstract-This paper presents a method that allows evaluating the performance of an optical fiber system where bit errors result from a complex interplay of spontaneous noise generated in optical amplifiers and birefringent disorder of the transmission fiber. We demonstrate that in the presence of temporal fluctuations of birefringence characteristics, the bit-error rate (BER) itself is insufficient for characterizing system performance. Adequate characterization requires introducing the probability distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…This derivation follows the method derived in [20], and it is already presented in [16], but for the sake of completeness we shall repeat it here.…”
Section: Instanton Methodsmentioning
confidence: 95%
“…This derivation follows the method derived in [20], and it is already presented in [16], but for the sake of completeness we shall repeat it here.…”
Section: Instanton Methodsmentioning
confidence: 95%
“…These systems can be accurately described by a Langevin equation when the typical time scale of the system is slow compared to the relaxation time of the coupled bath [23,15,33]. Because of the generality of this setup, Langevin dynamics have found applications in a prodigious array of fields including chemistry [23,17], biology [2,3], finance [5,26,21], and certain engineering applications [14,9,27]. It is the ubiquitous nature of the Langevin framework that allows such a pervasive grasp across the physical sciences.…”
Section: Introductionmentioning
confidence: 99%
“…Adequate characterization requires introducing the probability distribution function (PDF) of the (BER) obtained by averaging over many realizations of birefringent disorder. Theoretical analysis showed that this PDF has an extended tail indicating the importance of anomalously large values of (BER) [6]. In this article, numerical investigated had been carried and for the effects of PMD on an optical communication layout, taking into account the fiber length, bit rate, and laser diode characteristics.…”
Section: Introductionmentioning
confidence: 99%